Using parametric mapping to assess the impact of stroke rate on the upper limb kinematics in swimming - Simbana, D.; Seifert, L.; Hellard, P.; Guignard, B. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Coordination between propulsive actions of the left and right arms is highly correlated to Stroke Rate SR, Speed V, v fluctuations, and power output (Seifert et al. 2015). Simbana et al. 2020 found that females swimmers had difficulty to follow the imposed SR. The purpose of this case study is to use parametric mapping (SPM) to explore the impact of imposed stroke rate on upper limbs swim cycle kinematics